Outpatient follow-up of stroke patients: A systematic review - Hu, Zhonghua; Hongyan Zhao; Yu, Tianhao; Gu, Qingxin; Xi, Yingxue; Ye, Tian; Wang, Rui (Journal of the Pakistan Medical Association, 2025)
Objective: To summarise the best evidence of outpatient follow-up of stroke patients, and to provide a reference for clinical practice. Method: The current systematic review was conducted in November 2024 in China and comprised literature search done across a range of databases, including Guideline International Network, National Guideline Clearinghouse, China Guideline Clearinghouse, National Institute for Clinical Medicine, Joanna Briggs Institute Evidence-based Nursing Centre Library, Best Practice, Registered Nurses’ Association of Ontario, PubMed, Excerpta Medica dataBASE, Web of Science, Cochrane Library, Chinese National Knowledge Infrastructure, WanFang Data and China Biology Medicine disc. The search targeted studies reporting data on the outpatient follow-up of patients with cerebral apoplexy. Results: Of the 14 studies, 1(7.14%) involved clinical decision-making, 7(50%) were guidelines, and 2(14.28%) each were systematic reviews, expert consensus, and randomised controlled trials. The studies identified 33 best pieces of evidence across 6 categories for outpatient follow-up of stroke survivors after discharge. Conclusions: The review summarised the best pieces of evidence and provided a reference for standardised outpatient follow-up for stroke patients. Key Words: Stroke, Outpatient, Follow-up studies, Evidence-based nursing.